Tadresi mawnat Resource Pack-URDU TERM -2 KG (THE CITY SCHOOL PAKISTAN)
Recognition of additional Urdu letters (typically from middle to end of the alphabet, depending on the pace set in Term 2). Vocabulary development (fruits, animals, body parts, colors, family members, etc.). Listening and responding to simple Urdu instructions and greetings. Singing Urdu rhymes and participating in language games. Practicing correct pronunciation of Urdu phonemes.
Building familiarity with Urdu sounds, letters, and simple vocabulary through play-based, multi sensory learning
Shelving location: M4
At this stage, children are developing listening and speaking skills in their first or additional language (Urdu). They are learning through repetition, imitation, play, and interaction with familiar adults and peers. Most children are still building vocabulary and confidence in oral expression.
Keywords: TCS Urdu Resource Pack; Urdu text book Term 2